Analysis of Kazakhstan's Master's Program Implementation Experience with a View to Sharing Best Practices Among EAEU Members (Using Russia as an Example) (International relations and international law Journal, 2025)
Modern socio-political processes and the transformation of the educational systems of the EAEU countries actualize the task of mutual exchange of best practices in the field of higher education, which act as elements of “soft power” in international relations. Within the context of Eurasian integration, the analysis of the experience of implementing master's programs in Russia's strategic partner – Kazakhstan is particularly significant. The focus on Kazakhstan's experience is due to its key role in the EAEU, close historical and economic ties with Russia, and large-scale academic mobility between the countries. Kazakh master's programs demonstrate growing competitiveness, evidenced by their inclusion in international rankings.The article provides an analysis of the experience of implementing master's programs at leading universities in Kazakhstan (three state and two private), conducted by a team from the Peoples' Friendship University of Russia named after Patrice Lumumba, based on open sources and interviews with administration representatives.The article describes the features of Kazakhstan's state policy in higher education amid Eurasian integration and global challenges, presents the most outstanding master's programs, shows the specifics of admission, development, implementation, and examination of educational programs, and aspects of graduate employment.After analyzing the data, the authors have developed a number of recommendations that could be implemented at Russian universities (using RUDN University as an example) to improve the quality of master's programs and deepen educational cooperation within the EAEU framework.Key words: Russia, Kazakhstan, EAEU, magistracy, Higher education, educational integration, experience sharing, best practices, international relations.